More teachers, smarter students? Potential side effects of the German educational expansion - Matthias Westphal (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
In this paper, I evaluate potential side effects of the educational expansion in Germany on the learning outcomes of today's students. The educational expansion was a demand shock in the labor market of teachers, which could have thus encouraged individuals with different teaching abilities to eventually become teachers. I find that replacing a non-affected teacher with an educational expansion teacher leads to a 2 percent reduction in students' test scores. Explorative analyses suggest that these teachers are more extrinsically rather than intrinsically motivated. The results highlight that monitoring and investing in quality is important for future extensions of public institutions. – – In dieser Studie evaluiere ich mögliche Nebeneffekte der weitestgehend abgeschlossenen Bildungsexpansion in Deutschland auf Lehrstandserhebungen heutiger Schüler. Die Bildungsexpansion kann als ein Nachfrageschock im Arbeitsmarkt für Lehrer angesehen werden. Dieser Nachfrageschock könnte neue Personen mit anderen Fähigkeiten dazu gebracht haben, den Beruf des Lehrers zu ergreifen. Meine Ergebnisse zeigen, dass diese neuen Lehrer die Lehrstandserhebungen ihrer heutigen Schüler um 2% senken. Zusätzliche Analysen belegen unter anderem, dass diese Lehrer zusätzlich eher extrinsisch als intrinsisch motiviert sind. Insgesamt heben die Ergebnisse hervor, dass die Güte von öffentlichen Institutionen und die Eignung ihrer Mitarbeiter ein wichtiger Aspekt ist, den man bei den zukünftig erforderlichen Erweiterungen dieser Institutionen verstärkt im Blick haben sollte.
Keywords: H75; I20; I21; I28; 330; human capital acquisition; teacher effectiveness; educational expansion